2022
DOI: 10.1101/2022.08.31.506043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neuroepithelial wave of BMP signalling drives anteroposterior specification of the tuberal hypothalamus

Abstract: The tuberal hypothalamus houses several major hypothalamic nuclei, dozens of transcriptionally distinct cell types, and clinically relevant cell populations implicated in obesity and related metabolic disorders. Building on recent advances in the field, here we draw upon transcriptional, signalling, and fate mapping analyses of chicken embryos and neuroepithelial explants to analyze tuberal hypothalamic development. We show that a wave of BMP signalling sweeps through early floor plate-like progenitors overlyi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 71 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…The exploration of embryonic tanycytes is limited by their difficulty to be set apart from neural pogenitors, here we managed a good separation between these two by mapping human embryonic data onto a mouse reference data where tanycyte were clearly characterised. We found that comparing to RAX+ neural progenitors (SHH+, occur mostly at early embryonic stages), tanycytes express more radial glial genes FABP7, astrocyte marker AQP4, GFAP as well as tanycyte markers DIO2, CRYM, FRZB (Figure 2), in consistent with their radial glia-like identity as well as their function (Chinnaiya et al 2022). Regarding human tanycyte heterogeneity, we identified similar tanycyte subtypes (α and β) to adult rodent tanycytes, though their gene expression profiles are slightly different that may reflect both species difference and/or functional maturity, for example, DIO2 and FGFR1 are more highly expressed in β tanycyte in adult mouse (Campbell et al 2017), but in human embryonic tanycyte, they are similarly expressed in both α and β tanycytes (Figures 3 & S3).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The exploration of embryonic tanycytes is limited by their difficulty to be set apart from neural pogenitors, here we managed a good separation between these two by mapping human embryonic data onto a mouse reference data where tanycyte were clearly characterised. We found that comparing to RAX+ neural progenitors (SHH+, occur mostly at early embryonic stages), tanycytes express more radial glial genes FABP7, astrocyte marker AQP4, GFAP as well as tanycyte markers DIO2, CRYM, FRZB (Figure 2), in consistent with their radial glia-like identity as well as their function (Chinnaiya et al 2022). Regarding human tanycyte heterogeneity, we identified similar tanycyte subtypes (α and β) to adult rodent tanycytes, though their gene expression profiles are slightly different that may reflect both species difference and/or functional maturity, for example, DIO2 and FGFR1 are more highly expressed in β tanycyte in adult mouse (Campbell et al 2017), but in human embryonic tanycyte, they are similarly expressed in both α and β tanycytes (Figures 3 & S3).…”
Section: Discussionmentioning
confidence: 68%
“…Differentially expressed gene analysis shows that tanycyte marker genes CRYM, MT2A and FRZB (Campbell et al 2017) were unregulated in embryonic tanycytes, while anterior tuberal hypothalamus progenitor markers HES5 and SHH (Chinnaiya et al 2022) were upregulated in the neural progenitor clusters (Figure 2_A, Table S2). Apart from that, astrocyte markers SLC1A3/GLAST, FABP7/BLBP, GFAP, AQP4 and S100B were also expressed more in the tanycyte clusters comparing to the neural progenitor clusters (Figures 2 and 3_B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations